Tafsir Kontekstual Berwawasan Gender (Eksplorasi, Kritik dan Rekonstruksi) - Ahmad Faisal (Al-Ulum, 2013)
Although it is from the same reference of sources, the Qur’an and the Haditz, tafsir of gender relation in Islam constanly growing into various kinds. Among many important factors that forces the diversity is the different perspectives about involved contextual consideration in the tafsir processes. For many exegesists (mufassir) to approve it, the elements of historical and sosiological must be considerated in analyzed. If the elements are neglected then it may lead to bias and its result will be fragmented. Nonetheles, it still needs many efforts to sosializating it in more comprehensive and also to respond to any objections and outspoken critics from the society. The efforts also include to improve the methodological concept which are considered more comprehensive which integrate many approaches in Islamic Studies into main frame of methodological thought.